PENGARUH PRAKTIK PENGHINDARAN PAJAK TERHADAP NILAI PERUSAHAAN DAN BIAYA AGENSI DENGAN TRANSPARANSI INFORMASI SEBAGAI VARIABEL MODERATING (Studi empiris pada perusahaan manufaktur yang terdaftar di BEI tahun 2015-2017) - Citra Ratusan Asa; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2019)
This study aims to examined the effect of tax avoidance on firm value and agency costs with transparency of information as a moderating variable. The tax avoidance as an independent variable is measured by the Effective Tax Rate (ETR) and Book Tax Different (BTD). While the dependent variable in this study is the value of the company measured by Tobins'Q, and agency costs measured by Sales to Total Asset Ratio (STA). Transparency of information which is measured by 67 voluntary disclosure index. The selection of this research sample was conducted using a purposive sampling method in all Indonesian manufacturing companies listed on the IDX during 2015-2017. The number of final samples obtained was 153 consisting of 51 companies over a period of 3 years. Testing this sample uses a multiple regression analysis model. Overall, the results of the study indicate that the practice of tax avoidance with BTD and ETR proxies does not have a significant effect on firm value. The practice of tax avoidance with BTD proxy does not affect agency costs, but if the BTD proxy tax avoidance practices have a significant and positive effect on agency costs. Then information transparency reinforces that there is no relationship between tax avoidance  and firm value.